2001
DOI: 10.1090/s0002-9939-01-06155-x
|View full text |Cite
|
Sign up to set email alerts
|

A question of B. Plotkin about the semigroup of endomorphisms of a free group

Abstract: Let F F be a free group of finite rank n ≥ 2 n \geq 2 , let E n d ( F ) End(F) be the semigroup of endomorphisms of F F , and let A u t ( F ) Aut(F) be the group of automorphisms of F F . Theorem. If T : E n d ( F ) → E n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 5 publications
0
16
1
Order By: Relevance
“…In particular, we prove, that the groups Aut(End(B(m, n))) and Aut(End(B(k, n))) are isomorphic if and only if m = k. This is a particular problem about End(A), for A a free algebra in a certain variety, was raised by B.I.Plotkin in [14]. Analogous problems for End(F ) with F a finitely generated free group or free monoid were solved by Formanek in [12] and Mashevitzky and Schein in [13] respectively.…”
mentioning
confidence: 99%
“…In particular, we prove, that the groups Aut(End(B(m, n))) and Aut(End(B(k, n))) are isomorphic if and only if m = k. This is a particular problem about End(A), for A a free algebra in a certain variety, was raised by B.I.Plotkin in [14]. Analogous problems for End(F ) with F a finitely generated free group or free monoid were solved by Formanek in [12] and Mashevitzky and Schein in [13] respectively.…”
mentioning
confidence: 99%
“…In the case when Θ is a variety of all groups we have the classical results which let us resolve this problem by an indirect way. In [3] proved that for every free group Fi the group Aut (AutFi) coincides with the group Inn (AutFi), from this result in [4] was concluded that Aut (EndFi) = Inn (EndFi) and from this fact by theorem of reduction [2] it can be concluded that AutΘ 0 = InnΘ 0 . In the case when Θ = N d is a variety of the all nilpotent class no more then d groups we know by [6], that if the number of generators i of the free nilpotent class d group N F d i are bigger enough than d, then Aut AutN F d i = Inn AutN F d i .…”
mentioning
confidence: 93%
“…Schreier [4] and Mal'cev [5] have described all automorphisms of End(X), where X is a set, and Gluskin [6] has described the automorphisms of End(V), where V is a vector space. More examples are provided by, among others, Formanek [7], Levi [8,9], Liber [10], Magill [11], Mashevitzky and Schein [12], Schein [13], Sullivan [14], and Sutov [15]. Recently, the subject has attracted renewed attention owing to its links with universal algebraic geometry (see, for instance, [16]).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we focus on the power set ring. Our work is motivated on one hand by [3,[6][7][8]11,17,[19][20][21][22][23][24], where the authors have studied some questions related to the semigroup of endomorphisms of some rings, especially Boolean rings, and on the other hand by the importance of finding automorphisms of some semigroups and some (finite) rings, as explained above.…”
Section: Introductionmentioning
confidence: 99%